Students’ Language Anxiety Levels and Factors in Using ELSA Speak for Grade Eight at SMP Santo Thomas 3 Medan - Saragih, Fransiska; Lubis, Safrida (Universitas Negeri Medan, 2025)
This study investigates the levels of students’ language anxiety and its contributing factors in using ELSA Speak, an AI-powered mobile application for English speaking practice. Conducted among 26 eighth-grade students at SMP Santo Thomas 3 Medan, the research applied a qualitative method utilizing the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire and in-depth interviews. The findings revealed that most students experienced mild to relaxed levels of anxiety when using ELSA Speak. Only one student reported an anxious level, while none fell into the very anxious category. Three primary factors contributing to students’ language anxiety were identified: communication apprehension, test anxiety, and fear of negative evaluation. Notably, test anxiety appeared across all anxiety levels, indicating its strong influence in technology-assisted language learning. The study concludes that while ELSA Speak reduces extreme anxiety, the embedded scoring and feedback system remains a source of pressure for learners. Recommendations are made for educators to create supportive learning environments and for application developers to consider the psychological impacts of evaluative features in educational technologies.